Radiation balance at the surface in the city of So Paulo, Brazil: diurnal and seasonal variations - Ferreira, Mauricio Jonas; de Oliveira, Amauri Pereira; Soares, Jacyra; Codato, Georgia; Barbaro, Eduardo Wilde; Escobedo, João Francisco [UNESP] (Springer Wien, 2012)
The main goal of this work is to describe the diurnal and seasonal variations of the radiation balance components at the surface in the city of So Paulo based on observations carried out during 2004. Monthly average hourly values indicate that the amplitudes of the diurnal cycles of net radiation (Q*), downwelling and upwelling shortwave radiation (SWDW, SWUP), and longwave radiations (LWDW, LWUP) in February were, respectively, 37%, 14%, 19%, 11%, and 5% larger than they were in August. The monthly average daily values indicate a variation of 60% for Q*, with a minimum in June and a maximum in December; 45% for SWDW, with a minimum in May and a maximum in September; 50% for SWUP, with a minimum in June and a maximum in September; 13% for LWDW, with a minimum in July and a maximum in January; and 9% for LWUP, with a minimum in July and a maximum in February. It was verified that the atmospheric broadband transmissivity varied from 0.36 to 0.57; the effective albedo of the surface varied from 0.08 to 0.10; and the atmospheric effective emissivity varied from 0.79 to 0.92. The surface effective emissivity remained approximately constant and equal to 0.96. The albedo and surface effective emissivity for So Paulo agreed with those reported for urban areas in Europe and North America cities. This indicates that material and geometric effects on albedo and surface emissivity in So Paulo are similar to ones observed in typical middle latitudes cities. on the other hand, it was found that So Paulo city induces an urban heat island with daytime maximum intensity varying from 2.6A degrees C in July (16:00 LT) to 5.5A degrees C in September (15:00 LT). The analysis of the radiometric properties carried out here indicate that this daytime maximum is a primary response to the seasonal variation of daily values of net solar radiation at the surface.